Hematological, parasitological and biochemical parameters in sheep during the peripartum period - David, Caroline M. G.; Costa, Ricardo L. D.; Parren, Guadalupe A. E.; Rua, Miguel A. S.; Nordi, Ellen C. P.; Paz, Claudia C. P.; Quirino, Celia R.; Figueiredo, Rogério S.; Bohland, Elizabeth (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Pregnancy in all animal species requires special care and attention. During this period there is great variation in hematological and biochemical parameters. Many times these parameters are misinterpreted as being obtained from nonpregnant animals with unknown parasite status. Objective: To characterize the hematological, biochemical, and parasitological values within the peripartum period of Santa Ines sheep naturally infected. Methods: For this purpose, 45 ewes were used, with an average body weight of 50 kg. Data were collected during pregnancy, birth and, lactation. Measurements included body weight, body condition score (BCS), evaluation of conjunctive staining, and collection of blood and feces. Results: All variables changed throughout physiological stages. Weight and BCS were different between periods (p<0.05). Fecal egg counts (FEC) were higher in the peripartum period, with a predominance of Haemonchus ssp, 92.85%. Mean hematological and biochemical values varied throughout the study, (p>0.05). Conclusion: The influence of peripartum on the parameters studied should be considered and its use as a reference value. Regarding the physiological variations observed during peripartum, proper animal management could help minimizing the negative effects of parasitic infections on productivity.